L’émergence de la missiologie comme discipline critique du fait missionnaire à l’époque contemporaine - Jean-François Zorn (Cahiers d'Études du Religieux- Recherches Interdisciplinaires)
Missiology, both as a taught discipline and a field of research, is a fairly recent development in the academic curriculum of French-speaking universities since it dates from the 1980s. How can we explain that this development occurred so late, whereas Protestant Germany instituted its first University Chair in missiology at the end of the nineteenth century ? Following some hypotheses of the French Protestant missiologist Édouard Vaucher (1847-1920), this paper presents some factors that might explain why contemporary missionary practice preceded missiological theory. Oversea missions were born at the beginning of the nineteenth century, following the religious Awakening. Missionaries feared that the findings of missiology be criticical of their practices and believed they were successful without the help of missiology. Through case studies from the « École des Missions de la Société des Missions protestantes française » (1822-1970), we will analyse the epistemological foundations of missiology as a contemporary discipline in theology.